Massaging the Contours of Poverty and General Malaise amid Opportunities: Zambian and African Writers - Pethias Siame; Jive Lubbungu; Christian Ehiobuche (PT ARRUS Intelektual Indonesia, 2023)
This paper addresses the question, 'Why is there a general malaise and impoverishment among writers in Zambia and Africa despite their sweat and well known good record?' Writing is supposed to be a lucrative undertaking. However, most writers in Zambia and Africa continue to massage the contours of poverty. This qualitative study discusses the views of the members of Writers Space Africa –Zambia (WSA). 25 writers and 2 online publishing companies were interviewed via the WhatsApp platform. The study employed a descriptive approach and thematic analysis. The study reveals that writers continue to court poverty due to lack of financial literacy, and heavy reliance on self-publishing. It also shows that most writers lack collaboration with big players in the book industry, not producing books in series and the readers' attitude towards reading. There is a lack of book adaptation by filmmakers while books are not being translated into other languages coupled with a lack of support systems by governments among other reasons, render writers to continue massaging impoverishment and general malaise. The study recommends robust support systems by governments and collaboration among writers to age out of the doldrums of general impoverishment among writers in Zambia and Africa.